Road to Avonlea. The complete fifth season [videorecording (DVD)] = Les contes d'Avonlea. L'intégrale de al cinquième saison - Sullivan, Kevin, 1955-; Grant, Trudy; Polley, Sarah; Burroughs, Jackie; Ruffman, Mag; Montgomery, L. M. (Lucy Maud), 1874-1942 (Sullivan Entertainment, 2011)
Sara has blossomed into an independent and self-assured young lady, but one that still has a penchant for trouble. Now a fully-integrated member of Avonlea society, she begins to think about the day she must leave the security of her new home. Once again, the stories in this volume range from uproariously funny to poignantly emotional.